"A world eternally under construction": Věra Chytilová and late-socialist Prague. Issue 3 (2nd September 2018) - Lovejoy, Alice
ABSTRACT: This essay examines two of Věra Chytilová's 'normalization'-era nonfiction and fiction films: the 1979 feature Panelstory, or The Birth of a Settlement ( Panelstory, aneb Jak se rodí sidlíště, 1979) and the short experimental documentary Time is Inexorable ( Čas je neúprosný ), produced a year earlier. Each of these films plays out in the half-finished buildings and construction sites of late-1970s Prague, a city whose periphery was marked by large-scale prefabricated housing developments ('a world', in Bohumil Hrabal's words, 'eternally under construction'). The essay reads both films closely, analyzing their aesthetic, narrative, and conceptual links to other cinematic and literary engagements with late-socialist Prague and its architecture: Daniela Hodrová's theoretical essays and trilogy of novels City of Torment (Trýznivé město ), Hrabal's Too Loud a Solitude ( Příliš hlučná samota, 1977), and Václav Táborský's documentary City of Mud ( Zablácené město, 1963). The essay argues that, taken together, these texts offer a clear-eyed reading of late-socialist urban space, and the complex temporal and historical questions embedded within it.